Penerapan Konsep CO-PRODUCTION dalam Pelayanan Publik di Kota Gorontalo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This research specifically examines how the involvement of the community in the process of digitizing services at the population and civil registration office of Gorontalo City. Co-production is a collaboration between the government and the community to improve the quality, effectiveness, and satisfaction of services. The main problems in this study are the low participation of the community in population administration and challenges in the efficiency of services and the use of digital technology. The method used is qualitative descriptive through observation, interviews, and documentation. The results of the study show that co-production has been implemented through community involvement in data verification, the use of digital services, and active communication between officers and the community. However, there are still obstacles such as low digital literacy and limited human resources. In addition, technology infrastructure and internet access factors also affect the optimization of digital services. This study concludes that co-production is able to increase the effectiveness, responsiveness, and accountability of public services, although efforts are still needed to increase institutional capacity and community participation in a sustainable manner as well as a more inclusive digital education strategy.